1. Question:উৎপাদকে বিশ্লেষণ কর: `(3a + 1)^3 - (2a - 3)^3` 

    Answer
    `(3a + 1)^3 - (2a - 3)^3`
    
      `= {(3a + 1) - (2a - 3)} {(3a + 1)^2 + (3a + 1) (2a - 3) + (2a - 3)^2}`
    
      `= (3a + 1 - 2a + 3) {(3a)^2 + 2.3a. 1 + (1)^2 + 3a. 2a + 1. 2a`
    
                                `- 3.3a - 3 + (2a)^2 - 2.2a .3 + (3)^2}`
    
       `= (a + 4) (9a^2 + 6a + 1 + 6a^2 + 2a - 9a - 3 + 4a^2 - 12a + 9`
    
       `= (a + 4) (19a^2 - 13a + 7)`   (Ans)






    1. Report
  2. Question:উৎপাদকে বিশ্লেষণ কর: `(x + 5) (x - 9) - 15` 

    Answer
    `(x + 5) (x - 9) - 15`
    
      `= x^2 + 5x - 9x - 45 - 15`
    
      `= x^2 - 4x - 60`
    
      `= x^2 - 10x + 6x - 60`
    
      `= x(x - 10) + 6(x - 10)`
    
      `= (x + 6) (x - 10)`  (Ans)






    1. Report
  3. Question:উৎপাদকে বিশ্লেষণ কর: `(x + 2) (x + 3) (x + 4) (x + 5) - 48` 

    Answer
    `(x + 2) (x + 3) (x + 4) (x + 5) - 48`
    
      `= (x + 2) (x + 5) (x + 3) (x + 4) - 48`
    
      `= (x^2 + 2x + 5x + 10) (x^2 + 3x + 4x + 12) - 48`
    
      `= (x^2 + 7x + 10) (x^2 + 7x + 12) - 48`
    
       ধরি, `x^2 + 7x + 10 = a`
    
      :.প্রদত্ত রাশি,
    
        `= x^2 + 7x + 12 = x^2 + 7x + 10 + 2 = a + 2`
    
        `= a(a + 2) - 48`
    
        `= a^2 + 2a - 48`
    
        `= a^2 + 8a - 6a - 48`
    
        `= a(a + 8) - 6(a + 8)`
    
        `= (a + 8) (a - 6)`
    
        `= (x^2 + 7x + 10 + 8) (x^2 + 7x + 10 - 6)`
    
                                            [a এর মান বসিয়ে]
    
        `= (x^2 + 7x + 18) (x^2 + 7x + 4)`
    
        `= (x^2 + 7x + 4) (x^2 + 7x + 18)`  (Ans)






    1. Report
  4. Question:দেখাও যে, `x^3 + 9x^2 + 26x + 24 = (x + 2) (x + 3) (x + 4)` 

    Answer
    বামপক্ষ  
      `= x^3 + 9x^2 + 26x + 24`
    
      `= x^3 + 9x^2 + 27x + 27 - x - 3`
    
      `= x^3 + 3.x^2.3 + 3.x.3^2 + 3^3 - (x + 3)`
    
      `= (x + 3)^3 - (x + 3)`
    
      `= (x + 3) {(x + 3)^2 - 1}`
    
      `= (x + 3) {(x + 3)^2 - (1)^2}`
    
      `= (x + 3) (x + 3 + 1) (x + 3 - 1)`
    
      `= (x + 3) (x + 4) (x + 2)`
    
      `= (x + 2) (x + 3) (x + 4)`
    
       = ডানপক্ষ
    
        `:. x^2 + 9x^2 + 26x + 24 = (x + 2) (x + 3) (x + 4)` (দেখানো হলো)






    1. Report
  5. Question:দেখাও যে, ` (x + 1) (x + 2) (3x - 1) (3x - 4) = (3x^2 + 2x - 1) (3x^2 + 2x - 8)` 

    Answer
    বামপক্ষ,  
     `= (x + 1) (x + 2) (3x - 1) (3x - 4)`
    
     `= (x + 1) (3x - 1) (x + 2) (3x - 4)`
    
     `= (3x^2 + 3x - x - 1) (3x^2 + 6x - 4x - 8)`
    
     `= (3x^2 + 2x - 1) (3x^2 + 2x - 8)`
    
        = ডানপক্ষ
    
       `:. (x + 1) (x + 2) (3x - 1) (3x - 4) = (3x^2 + 2x - 1) (3x^2 + 2x - 8)` (দেখানো হলো)






    1. Report
Copyright © 2025. Powered by Intellect Software Ltd